The History of the Drainage of the Great Level of the Fens, Called Bedford Level With the Constitution and Laws of the Bedford Level Corporation - Wells, Samuel (Cambridge library collection. Technology, 1830)
Much of eastern England is below sea level, resulting in wide swathes of marshland that are easily flooded. In the seventeenth century, the Bedford Level Corporation was set up by Francis Russell, fourth earl of Bedford, in order to manage the drainage of the Great Level of the Fens, which became known as the Bedford Level and is the largest region of fenland in eastern England. Between 1828 and 1830, Samuel Wells, the corporation's registrar, published his well-documented history of the Bedford Level and the attempts made at various points to clear it of water using a variety of methods, from earthworks raised by the Romans to the strategies of Sir Cornelius Vermuyden and the eventual introduction of steam-powered technology. Volume 1, published in 1830, contains a historical account of the area and of the commission set up to address the perennial problem of flooding